2001
DOI: 10.1093/oxfordjournals.jbchem.a002839
|View full text |Cite
|
Sign up to set email alerts
|

Octamer Binding Protein-1 Is Involved in Inhibition of Inducible Nitric Oxide Synthase Expression by Exogenous Nitric Oxide in Murine Liver Cells

Abstract: Nitric oxide (NO) has diverse effects on immune responses and hepatic functions. In BNL CL.2 cells, the murine embryonic liver cells, inducible nitric oxide synthase (iNOS) mRNA expression appeared after 3 h of treatment with IFN-gamma and LPS. Interestingly, mRNA and protein expression of iNOS was down-regulated by sodium nitroprusside (SNP) and diethylamine dinitric oxide in a time- and dose-dependent manner, but not by H2O2. TNF-alpha gene expression was also dramatically reduced by SNP, but IL-6 gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These results suggest that triptolide inhibits the up-regulation of Oct-1 binding activity induced by LPS and PMA. The Oct-1 binding activity is regulated by protein modification such as phosphorylation or S-nitrosylation (31,43). Our results show that triptolide did not reduce the abundance of Oct-1 protein in the nuclear extract, suggesting that it inhibited Oct-1 binding activity induced by LPS and PMA by blocking Oct-1 protein modification.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…These results suggest that triptolide inhibits the up-regulation of Oct-1 binding activity induced by LPS and PMA. The Oct-1 binding activity is regulated by protein modification such as phosphorylation or S-nitrosylation (31,43). Our results show that triptolide did not reduce the abundance of Oct-1 protein in the nuclear extract, suggesting that it inhibited Oct-1 binding activity induced by LPS and PMA by blocking Oct-1 protein modification.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, it was possible that inhibition of NF-B, NF-AT, or AP-1 could play a role in suppressing iNOS transcription. It has been reported that mutation of the Oct-1 binding motif in the murine iNOS promoter completely inhibited iNOS transcription in BNL CL2 cells, whereas alteration of other binding sites had no effect on the promoter activity (27,31). and phorbol 12-myristate 13-acetate (PMA; 10 ng/ml) and in the absence or presence of Tript or Dex at the indicated concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the periods of incubation studied, LA and SA did not affect NF-jB activation but increased iNOS expression after 6 and 12 h, respectively. Other transcriptional factors are involved in iNOS expression, as the octamer factor (Oct) [54,55], signal transducer and activator of transcription-1a (STAT-1a) [56][57][58], cAMP-induced transcription factors such as cAMP-responsive element binding protein (CREB) and CCAAT-enhancer box binding protein (C/EBP) [59,60], and activating protein-1 (AP-1) [61]. SA and LA may have activated one of these transcriptional factors and increased iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare an NF-kB probe, oligonucleotides (59 GGCAACTGGGG ACTCTCCCTTT-39 and 59-GGCAAAGGGAGAGTCCCCAGTT-39) with an NF-kB binding site were labeled using the biotin 39 End DNA labeling kit (Pierce, Rockford, IL) and annealed as reported elsewhere (31). Nuclear extracts (8 mg) were incubated with the biotinylated DNA probe at room temperature for 30 minutes in 50 ng/ml poly (dI.dC), 2.5% glycerol, 5 mM MgCl 2 , 0.05% NP-40, and 20 fmol biotin-EBNA control DNA (Pierce).…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%